Meningkatkan Potensi Diri Siswa MA Melalui Komunikasi Efektif dan Inovasi Pembelajaran IPA Berbasis Nilai Islami di MA Plus Sunan Giri Salatiga - Ulfi Diana; Yuniar Fahmi Lathif; Ahmad Fahri Yahya Ainuri; Dianati, Yusrina; Dhimas Adhityasmara; Laela Rizki Fauzia; Putri Hapsari (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aimed to assess changes in the understanding of 10th-grade students at MA Plus Sunan Giri Salatiga following training on effective communication and science instruction integrated with Islamic values. Conducted on May 22, 2026, the activity was evaluated using a one-group pretest-posttest design; complete paired data were obtained for 46 students. The program included material presentation, interactive discussions, communication practice, the introduction of "science *shalawat*" (Islamic devotional songs), reflection, and comprehension assessment. Pretest and posttest scores were analyzed descriptively and via the Wilcoxon Signed Ranks Test. The mean score rose from 81.52 to 86.52. Wilcoxon results indicated a significant difference (Z = -2.094; p = 0.036) with an effect size of r ≈ 0.31. Scores increased for 21 students, decreased for 14, and remained unchanged for 11, indicating non-uniform participant responses. The stable median (90.00) and maximum score (100.00) across both measurements suggest a possible ceiling effect. While findings support a shift in understanding following the activity, the lack of a comparison group precludes causal attribution. This activity offers a participatory and contextual alternative for science education in *madrasas*, though further evaluation using more standardized instruments is warranted.